Evaluating Test-Retest Reliability of Language Tests in Moroccan Tertiary Education - El Kasri, Anouar Mohamed; Larouz, Mohammed; Maliki, Moulay Sadik; El Yousfi, Brahim (International Journal of Linguistics and Translation Studies, 2024)
Reliability is an essential element of assessment principles, and various methods were developed to measure language tests’ reliability, including test-retest. This method is widely discussed in the literature; however, no studies investigating test-retest reliability have been published in Morocco. Therefore, the present study evaluated the test-retest method in the Departments of English Studies in the Moroccan Faculties of Letters and Humanities. One thousand seven hundred and seventy-two semester one students from three Moroccan universities took the grammar, paragraph writing, spoken English, and study skills tests on two occasions. The data consisting of students’ scores in these modules were analyzed using descriptive statistics and reliability test analysis. The findings showed that variance among students and between test and retest scores was highly significant (p=0.001), and revealed that faculty, modules, and their interaction significantly affected the difference between test and retest scores. The implications of these results and the perspectives are discussed in the text.